Coping Strategies for Academic Pressure among Adolescents in Islamic Schools - Desi Ariska; Reza Fazan Dihaq (Psyche 165 Journal, 2026)
Academic stress is a common challenge experienced by students and may affect their psychological well-being and coping strategies. This study aims to explore students’ experiences of academic stress and the coping strategies they employ to manage academic demands. Using a qualitative research design, data were collected through semi-structured interviews with participants selected using purposive sampling. The data were analyzed using thematic analysis following Braun and Clarke’s framework. The findings revealed several sources of academic stress, including academic workload, performance expectations, and time management difficulties. In response to these stressors, students employed various coping strategies, such as problem-focused coping, emotion-focused coping, and religious coping. The results indicate that coping strategies play a crucial role in helping students manage academic stress and maintain psychological balance. This study contributes to the literature by providing an in-depth understanding of students’ subjective experiences of academic stress and coping, which may inform educational institutions in developing appropriate support programs. Keywords: Coping strategies; Qualitative research; Students; Psychological well-being